Risk of dyslexia and strategies of coping in socially difficult situations by younger school-aged children - Marzena Agnieszka Kowaluk-Romanek (Maria Curie-Skłodowska University, Lublin, Poland, 2019)
Own conducted studies complement the empirical approach to children's coping with difficult situations. Their aim was to answer the question whether and how the risk of dyslexia affects coping in socially difficult situations by younger school-aged children. The study covered 64 pupils from grades 2 and 3 of elementary schools in the lubelskie province. The core group was made up of pupils with diagnosed risk of dyslexia, and the comparative group was made up of their peers not having specific problems with learning. The studies revealed that there are statistically significant differences in the area of two scales: cooperation and avoidance. Children with a risk of dyslexia in socially difficult situations use the cooperation strategy definitely less seldom than their peers. Instead of an effective strategy of coping in stressful situations, they exhibit various defence methods not focused on resolving and overcoming the problem. An avoidance strategy predominates in this case. In comparison to their peers they definitely more frequently not take steps aimed at resolving a difficult situation. Children with a risk of dyslexia as well as children without learning difficulties use ineffective strategies of coping in difficult situations such as aggression and yielding with similar frequency.